Preparation and properties of polyether imide solvent-resistant ultrafiltration membrane - OUYANG Guozi; LI Xindong; ZHANG Xin; LI Haike; LI Lang; LI Wenhao; ZHONG Zhaohuang (Cailiao gongcheng, 2022)
Polyether imide (PEI) flat ultrafiltration membrane was prepared by immersion precipitation phase inversion method. The effects of polymer PEI concentration and additive polyvinylpyrrolidone (PVP) concentration on the structure and properties of membrane were investigated. In order to improve the solvent resistance of ultrafiltration membrane, hexamethylenediamine (HDA) was used for chemical crosslinking, and the difference of membrane performance under different crosslinking time was studied. The results show that the flux of the crosslinked membrane is effectively improved without reducing the membrane separation performance compared with the uncrosslinked ultrafiltration membrane. Under the operating pressure of 0.1 MPa, the flux of pure water is increased from 667.1 L/(m2·h) to 1126.1 L/(m2·h), while the rejection rate of 1.0 g/L BSA solution remains above 97%. After soaking in six different solvents for 48 h, it was found that the uncrosslinked membrane is completely dissolved in N, N-dimethylformamide (DMF), while the crosslinked membrane still maintains a good membrane morphology with an adsorption capacity of 0.86 g/g. The adsorption capacity in ethanol, isopropanol, n-hexane and 1 mol/L HCl solution is smaller than that of the uncrosslinked membrane, but is increased in 1 mol/L NaOH solution, which indicates that the prepared crosslinked membrane has good solvent resistance and strong acid resistance, but the strong alkali resistance becomes worse.